Emotional intelligence among dyslexic students : a case study - Kannamah Mottan (Institute of Education, International Islamic University Malaysia, 2010)
The purpose of this study was twofold (1) to study the nature or characteristics of dyslexic students and their problems in the learning environment in the school and (2) to give an insight on their emotional intelligence and how they apply it in the classroom. A vast body of studies exists on dyslexia and emotional intelligence, while there is little research on emotional intelligence among dyslexic students in Malaysia. Therefore, the researcher undertook qualitative technique case study using exploration, investigation, inquiry, and narrative analysis involving tools like semistructured questions and focused group interviews. Data was collected by means from four students in Year Four, three teachers, and a parent in an integrated dyslexia programme in a primary school in the Klang Valley. Finding showed dyslexic students have a combination of similar and varied characteristics as reported in other findings elsewhere. They had problems in academic subjects like English, Bahasa Malaysia and Mathematics. In addition, their emotional intelligence, applying Goleman's theory (1995) was varied. The study also indicated that if these children are taught emotional intelligence skills they have the potential to learn them. This research paves the way for other studies to be conducted in special education especially in children with dyslexia and how they can be trained to be excellent students.